Carbon Emissions Disclosure Mediates the Effect of Environmental Performance on Firm Value - Ni Kadek Piena Jayanthi Putri; Made Gede Wirakusuma (E-Jurnal Akuntansi, 2025)
This research aims to obtain empirical evidence of the influence of environmental performance on firm value with carbon emissions disclosure as a mediation variable. This research was conducted on all companies listed on the IDX and participated in the PROPER program in 2021-2022. The sampling method used nonprobability sampling and obtained samples of 75 companies. The data analysis techniques used path analysis test and sobel test with SPSS. The results of this study show that environmental performance does not affect firm value. However, environmental performance has a positive effect on the carbon emissions disclosure, carbon emissions disclosure has a positive effect on firm value, and carbon emissions disclosure can mediate the effect of environmental performance on firm value.